Endoskopowe usunięcie guza zatoki klinowej wchodzącego do szczytu oczodołu - Łysoń, Tomasz; Sieśkiewiecz, Andrzej; Mariak, Zenon; Bryl, Anna; Mariak, Zofia; Rogowski, Marek (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Thanks to recent technical refinements the orbital apex can be explored endoscopically and this approach is used for tumor biopsy in some specialized centers. Nevertheless, only a few instances of total tumor resection have been reported to date. In this contribution we report a case of a 64 years old woman in whom we used neuronavigated endoscopy and intraoperative Doppler sonography, for total removal of a tumor located in the sphenoid sinus and invading the orbital apex. The visual acuity improved from 5/16 to 5/6 and HP diagnosis was cystis spuria.